If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 9 = -6x + -3 Reorder the terms: 9 + -5x = -6x + -3 Reorder the terms: 9 + -5x = -3 + -6x Solving 9 + -5x = -3 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + -5x + 6x = -3 + -6x + 6x Combine like terms: -5x + 6x = 1x 9 + 1x = -3 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 1x = -3 + 0 9 + 1x = -3 Add '-9' to each side of the equation. 9 + -9 + 1x = -3 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = -3 + -9 1x = -3 + -9 Combine like terms: -3 + -9 = -12 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| 12-7j=-2 | | 12y-3y=7 | | 2(-1+x/3)=12 | | m^2+2m-1m-5m-10+1=0 | | 5+2j=-13 | | 3(x+4)=4x-5 | | -7a+11b= | | 15=m+-9 | | 5n^2+8n-36=0 | | p^2-2px+x^2=y^2 | | 4(x+3)=14 | | t*6-5=15 | | 20/35*45/4= | | 3(4x+6y)=15 | | a*4+4=14 | | M^2+2m-1m-5m-10-1=0 | | x(x+12)=32 | | 7-0.03x=1.72+1.75 | | [4+2]=6 | | (n+8m)(n+3m)-(n+m)(n-4m)=7x | | 5x-2x+6=x+18 | | 3(4-3c)=c-6 | | 3p+5=2p+15 | | 8*x=72 | | -7(f+1)-6=-41f+55 | | x(x-3)(x+3)=0 | | .4y=9 | | 2z+3(x-5)=130 | | 8y-4=36 | | 2x^3-2x^2+6x-6=0 | | 7x-2=-21 | | c(N)=25+0.15 |